DISPUTES REGARDING THE DERIVATION OF RULINGS FROM CUSTOMS AMONG ISLAMIC SCHOOLS OF THOUGHT AND THEIR SOLUTIONS - To’xtayev Nasrullo Nurullaevich (Bright Mind Publishing, 2025)
This article analyzes the disputes regarding the derivation of rulings from customs among various Islamic schools of thought. The differences between these schools arise in the interpretation of religious texts and the significance of customs in practice. These disputes are often linked to religious and cultural contexts, shaping diverse perspectives and attitudes within society. The article examines the causes of these disputes and explores potential solutions. The findings include recommendations aimed at enhancing compatibility among schools and strengthening religious unity.
Keywords: Schools of thought, customs, disputes, rulings, religious interpretation, culture, compatibility, religious unity, society.